Yield and Physicochemical Properties of Soluble Dietary Fiber Extracted from Untreated and Steam Explosion-Treated Black Soybean Hull - Meng Shen; Yunfei Ge; Ziyue Kang; Zhigang Quan; Juan Wang; Jinling Xiao; Weihao Wang; Longkui Cao (Journal of Chemistry)
Black soybean hull was subjected to steam explosion (SE) treatment under different conditions to improve the yield and properties of soluble dietary fiber (SDF) extract. Optimal conditions for SE treatment were found to be moisture content of 15%, pressure level of 1.0 MPa, and treatment time of 80 s. Under these conditions, the yield of SDF increased from 10.20% to 17.49%. In addition, structural and functional properties of SDF from untreated and SE-treated black soybean hull were investigated. Soluble dietary fiber extracted from SE-treated hull exhibited lower molecular weight and improved functional properties, such as cholesterol-binding capacity, when compared to SDF extracted from untreated soybean hull. In addition, SDF extracted from SE-treated black soybean hull showed a rough surface structure, while a smooth surface structure was found for SDF extracted from the untreated hull. The obtained results indicate that SE treatment can be successfully used to enhance the yield and the property of yolk cholesterol absorption of SDF adsorption of yolk cholesterol functional properties of SDF from black soybean hull.